Exploring the Potential of Concept Associations for the Creative Generation of Linguistic Artifacts: A Case Study With Riddles and Rhetorical Figures - Francisco, Virginia; Hervás, Raquel; Méndez, Gonzalo; Galván, Paloma (Frontiers in Psychology, 2018)
Automatic generation of linguistic artifacts is a problem that has been sporadically tackled over the years. The main goal of this paper is to explore how concept associations can be useful from a computational creativity point of view to generate some of these artifacts. We present an approach where finding associations between concepts that would not usually be considered as related (for example life and politics or diamond and concrete) could be the seed for the generation of creative and surprising linguistic artifacts such as rhetorical figures (life is like politics) and riddles (what is as hard as concrete?). The quality and appropriateness of the generated figures and riddles has been evaluated using human evaluators, and the results show that the concept associations obtained are useful for creating these kinds of creative artifacts.